Pendampingan Cipta Wirausaha Baru Desa Migran Melalui Program Tenaga Kerja Mandiri (TKM) di Desa Losari Rawalo Banyumas - Imam - Alfi; Kuswantoro - - (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
The New Entrepreneurial Creation Assistance Program is a program organized and facilitated by the Government in order to increase the productivity and skills of migrant villagers. This program is intended for families who are left behind by their husbands/wives who work abroad or who have retired as Indonesian Migrant Workers (TKI). The existence of a companion for Independent Workers (TKM) is important. Facilitators in community empowerment as facilitators, communicators, and dynamists. This study aims to describe the Implementation of New Entrepreneurial Creation Assistance through the Independent Manpower Program (TKM) in Losari Rawalo Village, Banyumas. This type of research is qualitative with a descriptive approach. The population of this research is the members of new entrepreneurs who are determined through snowball sampling. The informants are 5 program participants. Collecting data using interview techniques, documentation and observation. Data analysis used qualitative content analysis. The researcher uses the validity of data source triangulation which aims to explore the truth of the data/information based on various different data sources. Based on the results of the study, it can be concluded that First: The presence of the New Entrepreneurial Assistance Program through the Independent Manpower Program (TKM) is very helpful for ex-TKI and their families to be more productive and have skills in entrepreneurship both while living working abroad or when they return home and work. settled in his hometown. Second: TKM activities are activities that directly touch the community. The community immediately becomes an actor of empowerment while the Government is the regulator and provider of facilities. Residents are increasingly enthusiastic because the program is carried out openly and free of charge. Third; The business groups that are formed are in dire need of continuous assistance. Long-term expectations of groups that have been formed can develop